ESCHERICHIA COLI CONTAMINATION ON IMPORTED FROZEN BUFFALO MEAT SOLD AT AIKMEL TRADITIONAL MARKET, AIKMEL DISTRICT, EAST LOMBOK DISTRICT, WEST NUSA TENGGARA PROVINCE - Rahmat Ade Verdiasyah; Hapsari Mahatmi; I Made Sukada; Gede Putra Sanjaya (Buletin Veteriner Udayana, 2024)
The demand for beef in Indonesia continues to increase. The government is striving to achieve self-sufficiency in beef production, but the high price of beef is driving imports of buffalo meat from India. Buffalo meat has high nutritional value, similar to beef. Since 2015, frozen buffalo meat imports from India have begun to enter Indonesia, particularly in West Nusa Tenggara, as an effort to meet market demand in the modern shopping areas in Mataram City, Lombok. The relatively cheap price of frozen buffalo meat has led to expanded marketing in East Lombok, especially in the traditional market of Aikmel, which is approximately 72 km away from Mataram. The aim of this research is to determine the extent of Escherichia coli contamination and the amount of Escherichia coli contamination per gram of buffalo meat sold in this traditional market. The research samples consist of frozen buffalo meat from India sourced from 10 Indian buffalo meat vendors in the Aikmel market, each weighing 100 grams. The isolation and identification method follows Jawetz et al. (2008), starting with isolation on Eosin Methylene Blue Agar (EMBA), followed by identification with INMVIC (Indole, Methyl Red, Voges Proskauer, Citrate), reinforced by results from TSIA (Triple Sugar Iron Agar) and Urease tests. The research found that E. coli contamination exceeded the specified limit (SNI 7388:2009, 2009) in 9 out of 10 samples taken from 10 Indian buffalo meat vendors in the Aikmel market. The smallest and largest amounts of E. coli contamination in 90% of the contaminated samples were 80x101 and 7x103 colonies/gram, respectively. This condition is crucial for the government to pay attention to, in order to enhance education and supervision of the public regarding the procedures and regulations for the sale of frozen buffalo meat from India, in accordance with the marketing of animal origin products.